La relation linguistique en Écosse : multilinguisme et scotticité - Jean BERTON (E-REA)
This contribution addresses the linguistic relation in Scotland within the Scottish nation, within the UK and with foreign nations. It examines even aspects of that relation: Scotland’s resistance to imperial monolingualism; the rise of multilingualism, from relation to competition; from plurilingualism to multilingualism; linguistic relation through translations; tongues and languages in cultural relation; and Scottishness and native languages.